2005
DOI: 10.1111/j.1439-0264.2004.00578.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphoquantitative Aspects of Nitrergic Myoenteric Neurons from the Stomach of Diabetic Rats Supplemented with Acetyl‐L‐Carnitine

Abstract: The NADPH-diaphorase (NADPH-d) positive myoenteric neurons from the body of the stomach of rats with streptozotocin-induced diabetes with or without supplementation with acetyl-L-carnitine (ALC) were evaluated. At the age of 105 days the animals were divided into four groups: normoglycaemic (C), normoglycaemic supplemented with ALC (CC), diabetic (D) and diabetic supplemented with ALC (DC). The supplementation with ALC (200 mg/kg body weight/day) to groups CC and DC was made during 105 days. After this period … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 26 publications
2
12
0
2
Order By: Relevance
“…Similar results were found by Freitas et al (12) , who observed a significant 37.9% reduction in neuronal density in the jejunum in diabetic animals compared with non-diabetic animals. Other studies performed by our group have analyzed different segments of the gastrointestinal tract, including the ileum (3,22,46) , proximal colon (15,24,25,34,39) , and stomach (14) and showed similar results. This reduction in the number of myenteric neurons results from hyperglycemia, which initiates several biochemical events, such as disturbances in the polyol pathway, formation of AGEs, activation of the protein kinase C and hexosamine pathways, and glycolysis.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Similar results were found by Freitas et al (12) , who observed a significant 37.9% reduction in neuronal density in the jejunum in diabetic animals compared with non-diabetic animals. Other studies performed by our group have analyzed different segments of the gastrointestinal tract, including the ileum (3,22,46) , proximal colon (15,24,25,34,39) , and stomach (14) and showed similar results. This reduction in the number of myenteric neurons results from hyperglycemia, which initiates several biochemical events, such as disturbances in the polyol pathway, formation of AGEs, activation of the protein kinase C and hexosamine pathways, and glycolysis.…”
Section: Discussionsupporting
confidence: 66%
“…Similar results were found by Pereira et al (22) in the ileum of rats using the same experimental model. Other studies did not find significant results with regard to the number of nNOS-immunoreactive neurons in different segments of the gastrointestinal tract, such as stomach (14) , distal colon (44) , and duodenum (13) . According to Pereira et al (22) , this subpopulation of neurons is highly resistant to the action of free radicals produced by DM-induced hyperglycemia, explaining the results described above, including our study of enteric neurons.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The STZ is a substance that induces the experimental diabetes and has been used to assess the behavior of neurons in the enteric nervous system of several gastrointestinal segments (Young et al 1992, Büttow et al 1997, Wrzos et al 1997, Zanoni et al 2003, Clebis et al 2004, Fregonesi et al 2005. In order to be effective in the diabetogenic activity it should be given in doses higher than 25mg/kg of body weight (Junod et al 1969).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental period longer than 90 days cause less weight gain for diabetic animals (Zanoni et al 2003, Clebis et al 2004, Fregonesi et al 2005, Silverio et al 2008.…”
Section: Discussionmentioning
confidence: 99%